2016
DOI: 10.22159/ijpps.2016.v8i9.12242
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Methylglyoxal: A Possible Alternative Treatment for Antibiotic Resistant Bacterial Infections

Abstract: <p><strong>Objective: </strong>Essential oils are of significant interest in today’s world of healthcare because these compounds have a variety of medicinal properties. In this study, we evaluated the <em>in vitro</em> antibiotic role of essential oils as a possible alternative treatment in combatting Methicillin-resistant <em>Staphylococcus aureus</em> (MRSA).</p><p><strong>Methods: </strong>In conjunction with carrier oils, three essential oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…Our results of IZD of cinnamon essential oil against E. coli (32 mm) are similar to those described by Nimje et al [31] (32 mm), Melo et al [32] (30 mm) and Zhu et al [34] (30 mm), and larger than those described by Zhang et al [19] (19 mm). Based on the results observed in the present study the IZD (38 mm) of cinnamon essential oil against S. aureus, our results are in agreement with those described by Melo et al [32] (40 mm) and Cieslak et al [33] (35 mm), and larger than those described by Zhu et al [34] (29 mm), Zhang et al [19] (28 mm) and Nimje et al [31] (21 mm). The main component of Cinnamon cassia oil used in this study was cinnamaldehyde (86%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results of IZD of cinnamon essential oil against E. coli (32 mm) are similar to those described by Nimje et al [31] (32 mm), Melo et al [32] (30 mm) and Zhu et al [34] (30 mm), and larger than those described by Zhang et al [19] (19 mm). Based on the results observed in the present study the IZD (38 mm) of cinnamon essential oil against S. aureus, our results are in agreement with those described by Melo et al [32] (40 mm) and Cieslak et al [33] (35 mm), and larger than those described by Zhu et al [34] (29 mm), Zhang et al [19] (28 mm) and Nimje et al [31] (21 mm). The main component of Cinnamon cassia oil used in this study was cinnamaldehyde (86%).…”
Section: Discussionsupporting
confidence: 93%
“…Several authors have reported the antibacterial activity of Cinnamon cassia essential oil [19,[31][32][33][34]. Our results of IZD of cinnamon essential oil against E. coli (32 mm) are similar to those described by Nimje et al [31] (32 mm), Melo et al [32] (30 mm) and Zhu et al [34] (30 mm), and larger than those described by Zhang et al [19] (19 mm).…”
Section: Discussionsupporting
confidence: 88%